Understanding switching intention of information systems users. Issue 4 (6th May 2014) - Asimakopoulos, Grigorios; Asimakopoulos, Stavros
Abstract : Purpose: – The purpose of this paper is to reveal the impact of usability and switching costs on user intention to switch information systems (IS), and to examine the mediating role of switching costs on the usability-intention to switch relationship. Design/methodology/approach: – Using structural equation modeling, the research hypotheses tested in the context of forecasting IS using a web-based survey of 205 business forecasters. Findings: – Results show that both perceived usability and switching costs negatively affect intention to switch; and switching costs, through specific constructs, mediate the relationship between usability and intention to switch IS. Research limitations/implications: – Further research is needed for a more comprehensive understanding of the role of switching costs and to test the model in a longitudinal study and across different types of IS. Originality/value: – This research contributes to a better understanding of the interplay between usability and switching costs factors and their impact on IS switching user intention. Based on the study findings, theoretical and practical implications for IS are identified and discussed.